Simple Prototype Design of Phytoremediation Installation in Small Pilot Scale of Acid Mine Drainage Passive Treatment - Arif Umami; Ni Kadek Ema Sustia Dewi; Ade Faris Mu'taz; Ja'far Taufik Amin (Journal of Sustainable Development Science, 2024)
Phytoremediation is usually applied to passively treat Acid Mine Drainage (AMD) by constructing a wetland. To increase the success of the AMD treatment method, laboratory trials were carried out on a pilot scale, and the experimental results were applied on an actual scale. Therefore, a simple design will be prepared for this research that replicates the wetland work system. This research aimed to produce a prototype that could be used for initial testing of phytoremediation on a smaller scale before being applied to field conditions. The installation design was created using Adobe Illustrator software. The trial lasted two months, using modified acid water and flowing it periodically as controlled droplets via an infusion tap into the media that used Typha sp and Pistia stratiotes L as phytoremediator agents. This equipment was tested with three acidity levels, 4, 5, and 6, repeated twice for two months. Results showed that the prototype was built using three buckets arranged in layers, each with its function. The phytoremediation process had successfully occurred in this study, and installation was suitable to support the process. There was a change in AMD acidity around the plants for five weeks and an increase in acidity the fourth week after treatment at the outlet. It could be seen that AMD with lower acidity levels resulted in greater plant damage in the sixth week, but Typha sp still showed resistance to an acidic environment.